Trends in sport and exercise psychology research: An integrated bibliometric and systematic literature review based on Scopus (2005–2025) - Yusuf Hidayat; Mohd Sofian Omar Fauzee; Norlena Salamuddin; Singha Tulyakul; Utku Işık; Hasmiza Abdul Majeed; Burhan Hambali; Dywa Ikal Mutaqin; Nadila Maesara (CV. FOUNDAE, 2026)
Background: Sport and Exercise Psychology (SEP) has evolved significantly as a scientific discipline, yet comprehensive mapping of its intellectual structure, thematic evolution, and research trends remains limited, particularly for the period encompassing recent methodological and conceptual advances. Aims: This study mapped the bibliometric landscape of SEP research indexed in Scopus (2005–May 2025) and synthesised high-quality empirical evidence to address six research questions, identifying knowledge gaps and future directions. Methods: A dual-method approach combined bibliometric analysis of 2,637 Scopus-indexed articles using VOSviewer software with a PRISMA-guided systematic literature review. The search strategy employed the query TITLE (“Sport and Exercise Psychology”) in the Scopus database, limited to English-language original research articles published between 2005 and May 2025. Bibliometric indicators included publication trends, citation patterns, author productivity (Lotka's Law), journal distribution (Bradford's Law), geographical contributions, and keyword co-occurrence networks. Thirty high-quality empirical studies were reviewed to address six research questions spanning motivation, identity, professional practice, mental health interventions, methodology, and psychological risks. Results: Annual publication growth averaged 13.43%, peaking at 293 articles in 2024. The United States, United Kingdom, and Australia dominated output (32% combined). “Physical activity,” “exercise,” and “mental health” emerged as dominant themes, reflecting expansion beyond performance psychology toward holistic wellbeing. Conceptual structure analysis revealed four primary dimensions: sport motivation and performance, exercise and mental health, youth sport and education, and cognitive aspects. The systematic review identified three cross-cutting themes: progressive methodological pluralism, tension between globalising professional standards and culturally responsive practice, and convergence of researcher epistemology with practitioner identity formation. Conclusion: SEP demonstrates robust growth and increasing methodological sophistication, yet geographical disparities, underrepresented populations, and research-practice gaps require strategic attention to enhance global applicability and the implementation of evidence-based practice. This study contributes to the field by presenting the first integrated bibliometric-systematic review of SEP over two decades, offering a two-method framework that combines structural mapping of knowledge production with a substantial synthesis of empirical evidence, and an approach that has been underutilized in previous SEP reviews.